Circulatory response to volume expansion and transjugular intrahepatic portosystemic shunt in refractory ascites: Relationship with diastolic dysfunction. Issue 12 (December 2015) - Filì, Daniela; Falletta, Calogero; Luca, Angelo; Hernandez Baravoglia, Cesar; Clemenza, Francesco; Miraglia, Roberto; Scardulla, Cesare; Tuzzolino, Fabio; Vizzini, Giovanni; Gridelli, Bruno; Bosch, Jaime
Abstract: Background: Cirrhotic cardiomyopathy may lead to heart failure in stressful circumstances, such as after transjugular intrahepatic portosystemic shunt (TIPS) placement. Aim: To examine whether acute volume expansion predicts haemodynamic changes after TIPS and elicits signs of impending heart failure. Methods: We prospectively evaluated refractory ascites patients (group A) and compensated cirrhotics (group B), who underwent echocardiography, NT-proBNP measurement, and heart catheterization before and after volume load; group A repeated measurements after TIPS. Results: 15 patients in group A (80% male; 54 ± 12.4 years) and 8 in group B (100% male; 56 ± 6.2 years) were enrolled. Echocardiography disclosed diastolic dysfunction in 30% and 12.5%, respectively. In group A, volume load and TIPS induced a significant increase in right atrial, mean pulmonary, capillary wedge pressure and cardiac index, and a decrease in systemic vascular resistance (respectively, 4.7 ± 2.8 vs. 9.9 ± 3.6 mmHg; 13.3 ± 3.5 vs. 21.9 ± 5.9 mmHg; 8.3 ± 3.4 vs. 15.4 ± 4.7 mmHg; 3.7 ± 0.7 vs. 4.6 ± 1 lt/min/m 2 ; 961 ± 278 vs. 767 ± 285 dyn s cm −5 ; and 10.1 ± 3.3 vs. 14.2 ± 3.4 mmHg; 17.5 ± 4 vs. 25.2 ± 4.2 mmHg; 12.3 ± 4 vs. 19.3 ± 3.4 mmHg; 3.4 ± 0.8 vs. 4.5 ± 0.91 lt/min/m 2 ; 779 ± 62 vs. 596 ± 199 dyn s cm −5, p  < 0.001 for all pairs). At 24 h, cardiopulmonary pressures returned towards baseline. Conclusions: Acute volume expansion predicted haemodynamic changes immediately after TIPS. All patients had adequate haemodynamic adaptation to TIPS; none developed signs of heart failure.